2019
DOI: 10.1186/s13048-019-0489-1
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA methylation suppresses expression of estrogen receptor 1 (ESR1) in ovarian endometrioma

Abstract: BackgroundIn ovarian endometriomas (OE), the expression statuses of various steroid hormone receptors are altered compared with their expression statuses in eutopic endometrium (EE). For example, in OE, the expressions of estrogen receptor 1 (ESR1), which encodes ERα, and progesterone receptor (PGR) are downregulated, while the expression of ESR2, which encodes ERβ, is upregulated. The causes of these changes are unclear. DNA methylation of a specific region of a gene can result in tissue-specific gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…Although the detailed mechanisms of the attenuation of ERα and the increase in ERβ remain unclear, previous studies showed hypomethylation of the ERβ promoter could be associated with upregulation of protein level in endometriotic tissues . Maekawa et al reported the aberrant DNA methylation of tissue‐dependent and differentially methylated region (T‐DMR) in ERα contributes to its impaired expression in the ovarian endometrioma . On the other hand, in contrast to a previous report, they concluded DNA methylation is not involved in the upregulation of ERβ in endometriosis .…”
Section: Estrogen Receptors In Endometriosismentioning
confidence: 91%
See 1 more Smart Citation
“…Although the detailed mechanisms of the attenuation of ERα and the increase in ERβ remain unclear, previous studies showed hypomethylation of the ERβ promoter could be associated with upregulation of protein level in endometriotic tissues . Maekawa et al reported the aberrant DNA methylation of tissue‐dependent and differentially methylated region (T‐DMR) in ERα contributes to its impaired expression in the ovarian endometrioma . On the other hand, in contrast to a previous report, they concluded DNA methylation is not involved in the upregulation of ERβ in endometriosis .…”
Section: Estrogen Receptors In Endometriosismentioning
confidence: 91%
“…Maekawa et al reported the aberrant DNA methylation of tissue‐dependent and differentially methylated region (T‐DMR) in ERα contributes to its impaired expression in the ovarian endometrioma . On the other hand, in contrast to a previous report, they concluded DNA methylation is not involved in the upregulation of ERβ in endometriosis . Interestingly, other investigators showed that ERβ downregulates ERα expression in the stromal cells from ovarian endometrioma .…”
Section: Estrogen Receptors In Endometriosismentioning
confidence: 92%
“…Disorders at the level of ESR2 gene expression associated with endometriosis and related to the types and sites of lesions have been confirmed by world literature reports. The team of Maekawa et al employed RT-PCR to assay the expression levels of ESR1, ESR2 and progesterone receptor (PGR) genes in cases of ovarian endometriosis and eutopic endometrium (15). The ESR1 and PGR expression levels were substantially lower, while the level of ESR2 gene expression was significantly higher in endometriosis than in normal endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that DNA hyper-methylation has a detrimental effect on endometrial receptivity in the presence of high progesterone (P4) levels during COH [21]. E2 and P4 induced decidualization of human endometrial stromal cell in vitro has been shown to exhibit DNAm changes [18,22]. However, the status of DNAm pro les in supraphysiological E2 levels during COH and their associations with changes in gene expression remain unknown.…”
Section: Introductionmentioning
confidence: 99%